Pengaruh Campuran Onggok, Sekam, Pati dan Bahan Humat terhadap Pertumbuhan Aspergillus niger dan Kemampuannya dalam Melarutkan Fosfat - Yudi Sastro; Donny Widianto; Irfan D. Prijambada (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2006)
The aims of this study were to investigate the effects of the mixture of tapioca waste, rice bran, starch (BOC), and humic substance (BH) on Aspergillus niger growth and its phosphate solubilizing capability. The experiment was conducted in Erlenmeyer flask containing 200 ml Pikovskaya liquid media and incubated on shaker with 100 rotaries per minute for nine days.  The Christmas Island phosphate rock was used as phosphate source.  Aspergillus niger YD 17 was taken from the Laboratory of Microbiology, Faculty of Agriculture, Gadjah Mada University. The experiment was arranged using factorial completely randomized design with three-replications (3x4x3). The level of BOC (i.e. 0, 2, and 4 g.l-1 media)   and BH   (i.e. 0, 1, 2, and 3 ml.l-1) were applied as experimental factors. Dry weight of mycelia and the soluble phosphate in media were parameters of Aspergillus niger growth. The results showed that BOC and BH increased the Aspergillus niger growth and its phosphate solubilizing capability (P£0.05). Four-gram of BOC and 3 ml of BH per litter of media were the best level for Aspergillus niger growth, while 4 g of BOC and 2 ml of BH was the best level for phosphorus solubilization capability.